1997
DOI: 10.1142/s0217751x97000505
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of Faddeev–Jackiw and Dirac Approaches for Gauge Theories

Abstract: The equivalence between the Dirac method and Faddeev-Jackiw analysis for gauge theories is proved. In particular we trace out, in a stage by stage procedure, the standard classification of first and second class constraints of Dirac's method in the F-J approach. We also find that the Darboux transformation implied in the F-J reduction process can be viewed as a canonical transformation in Dirac approach. Unlike Dirac's method the F-J analysis is a classical reduction procedure, then the quantization can be ach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 21 publications
0
61
0
Order By: Relevance
“…Initially the equivalence was discussed in cases when the systems have no constraints [11,12]; but, in a constrained system, the situation was not completely clear, and some argumentation was provided earlier [13,14] as regards the equivalence between the methods. However, recently was presented a proof [15] that the usual Faddeev-Jackiw method and Dirac method were not completely equivalent; namely, one showed that some constraints calculated in the Dirac formalism do not appear in the calculation in the Faddeev-Jackiw formalism.…”
Section: Introductionmentioning
confidence: 99%
“…Initially the equivalence was discussed in cases when the systems have no constraints [11,12]; but, in a constrained system, the situation was not completely clear, and some argumentation was provided earlier [13,14] as regards the equivalence between the methods. However, recently was presented a proof [15] that the usual Faddeev-Jackiw method and Dirac method were not completely equivalent; namely, one showed that some constraints calculated in the Dirac formalism do not appear in the calculation in the Faddeev-Jackiw formalism.…”
Section: Introductionmentioning
confidence: 99%
“…are identified as constraints of the theory, and they are not absorbed as it is present in Dirac's method being identified as pseudo-Goldston bosons. Furthermore, we could observe that we arrived to the constraints and the generalized brackets in less steps than Dirac's method, this means that [FJ] is in particular, for the theory under study, more economic than Dirac's procedure [24]. In this manner, we have stablished all the elements for studying the quantization aspects, for example, we can use Dirac's brackets or…”
Section: Conclussions and Prospectsmentioning
confidence: 99%
“…An observation that will be of relevance in what follows is that such canonical transformation in phase space in not canonical with respect to the Dirac bracket (11). This is precisely the trick used to construct a "canonical representation of the constraint surface" [11] where the first class constraints are realized as a subset of momenta and the second class constraints as a proper subset of fields and its associated momenta. In these coordinates the Dirac bracket takes the standard form of an ordinary Poisson structure in Darboux coordinates.…”
Section: Dirac Algorithmmentioning
confidence: 99%